Recent advances on the role of process variables affecting gelatin yield and characteristics with special reference to enzymatic extraction: a review - Ahmad, Tanbir; Ismail, Amin; Ahmad, Siti Aqlima; Abdul Khalil, Khalilah; Kumar, Yogesh; Adeyemi, Kazeem Dauda; Sazili, Awis Qurni (Elsevier BV, 2017)
Gelatin is a natural macromolecule material extracted by the thermal hydrolysis of collagen. Gelatin raw materials are pretreated with either acid or alkali to allow the swelling of collagen in order to increase the efficiency of gelatin extraction. Swelling of collagen and its subsequent solubilization is greatly influenced by the pH, temperature, and time applied during both pre-treatment and extraction process. The pretreating agents break the cross-links between collagen chains depending on their persistence leading to variations in molecular weight distribution in the resultant gelatins. An alternative approach to acid and alkali treatment is the use of proteolytic enzymes. Compared with the alkali and acid processes, the enzymatic process improves yield, reduces processing time and generates less waste. Papain, neutrase, bromelain, pepsin, proctase and crude proteases are used as pretreatment agents for gelatin extraction. Albeit higher gelatin yield was obtained, there were simultaneous degradation of α and β chains of the gelatin, which lowers the gelatin quality, particularly the gel strength. The degradation was caused by the continued action of added protease enzymes. Apart from these extraction factors, indigenous proteases and protease inhibitors affect the yield and quality attributes of gelatin. The factors and processing conditions affecting the efficiency of gelatin extraction and the quality attributes of gelatin are the subjects of this review.